Histone deacetylases in cancer metabolic reprogramming - Yu Hyun Jeon; Hyeyeong Seo; Ji Woo Youn; Jung Yoo; Sang Wu Lee; Soo Yeon Oh; So Hee Kwon (Experimental & Molecular Medicine, 2026)
Abstract Cancer cells undergo extensive metabolic reprogramming to sustain rapid proliferation and adapt to heterogeneous tumour microenvironments. These metabolic alterations are tightly linked to epigenetic regulation, which reshapes gene expression and cellular signalling mechanisms. Among epigenetic regulators, histone deacetylases (HDACs) have emerged as key modulators of cancer metabolic reprogramming. Along with their canonical roles in histone deacetylation, HDACs regulate non-histone substrates, including metabolic enzymes and transcription factors, thereby coordinating transcriptional and metabolic programmes. In this review, we summarize current insights into HDAC-mediated regulation of glucose, lipid and amino acid metabolism in cancer and discuss the metabolic mechanisms underlying the anticancer effects of HDAC inhibitors. Collectively, we propose an integrated framework in which HDACs function as central regulators of cancer metabolic reprogramming. We highlight the limitations of HDAC inhibitor studies and discuss the emerging importance of isoform-specific HDAC functions in reprogramming cancer-specific metabolic dependencies and therapeutic strategies.